2019
DOI: 10.3390/photonics6030100
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of Nanoplasmonic Optical Fiber Sensors Based on D-Type and Suspended Core Fibers with Metallic Nanowires

Abstract: The introduction of metallic nanostructures in optical fibers has revolutionized the field of plasmonic sensors since they produce sharper and fine-tuned resonances resulting in higher sensitivities and resolutions. This article evaluates the performance of three different plasmonic optical fiber sensors based on D-type and suspended core fibers with metallic nanowires. It addresses how their different materials, geometry of the components, and their relative position can influence the coupling between the loc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 21 publications
0
4
0
Order By: Relevance
“…The sensitivity of RI needs improvement. Santos et al [18] presents the performance analysis of a new geometry sensing configuration for RI, based on SPR in photonic crystal fiber D-type optical fiber with a thin gold layer, using the finite element method. The sensitivity is high; however, photonic crystal fibers are expensive.…”
Section: Ri Experimentsmentioning
confidence: 99%
“…The sensitivity of RI needs improvement. Santos et al [18] presents the performance analysis of a new geometry sensing configuration for RI, based on SPR in photonic crystal fiber D-type optical fiber with a thin gold layer, using the finite element method. The sensitivity is high; however, photonic crystal fibers are expensive.…”
Section: Ri Experimentsmentioning
confidence: 99%
“…a silver nanocolumn for refractive index sensing and achieved a maximum sensitivity of 8860 nm/RIU [6]. Recently, in order to provide a simple structure, Santos et al reported a suspended core optical fiber structure incorporating gold nanowire and achieved good sensitivity in comparison to the conventional single-mode fiber (SMF) [7]. In the same year, we have reported hollow core fiber (HCF) sensor consists of an AuNW and achieve an average sensitivity of 10560 nm/RIU for RI = 1.46-1.48 [8].…”
Section: Iintroductionmentioning
confidence: 99%
“…Fiber laser systems and nonlinear optical converters are in demand for a wide variety of applied and fundamental problems, including telecommunications, noninvasive medical diagnostics, laser surgery, sensing, spectroscopy, etc. [1][2][3][4][5][6][7][8][9][10][11][12][13][14][15].…”
Section: Introductionmentioning
confidence: 99%
“…Waveguide modes in microstructured fibers are formed as a result of the interference of waves arising from reflection and refraction at the refractive-index microinhomogeneities [18]. In addition to the widespread photonic crystal fibers, in which several regular layers of air holes or glass rods are located around the core [16,26,28], there are suspended-core fibers, in which a thin core is surrounded by one row of air holes with thin walls between them [14,26,[29][30][31][32][33][34][35]. In addition, the manufacture of solid microstructured fibers from low-temperature chalcogenide and tellurite glasses simultaneously was reported [36].…”
Section: Introductionmentioning
confidence: 99%